Analysis of Soybean Competitiveness in Landawe Sub-District North Konawe District - Yunus, Lukman (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2020)
This study aims to analyze the competitiveness of soybean farming in Landawe District, North Konawe Regency. The study was conducted in December 2019. The population in the study were all soybean farmers, amounting to 49 people. Determination of the sample using the census method. Types and sources of data in the study include primary data and secondary data. Data collection techniques used in research are direct interviews with respondents and literature studies. Variables in the study include revenue, tradable inputs, non-tradable inputs, production, private prices, and social prices. Analysis of the data used is the Policy Analysis Matrix (PAM). The results showed that soybean farming in Landawe Subdistrict, North Konawe District has competitive competitiveness, which is the value of the ratio of private costs (Private Cost Ratio) of 0.30 smaller than one, which means that to produce a product requires a smaller additional cost. However, it does not have comparative competitiveness because the value of the ratio of domestic resource cost ratio is greater than one, namely 5.07 which means inefficient farming